2018
DOI: 10.1073/pnas.1812536116
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein YTHDF3 suppresses interferon-dependent antiviral responses by promoting FOXO3 translation

Abstract: IFN–stimulated genes (ISGs) are essential effectors of the IFN-dependent antiviral immune response. Dysregulation of ISG expression can cause dysfunctional antiviral responses and autoimmune disorders. Epitranscriptomic regulation, such as N6-methyladenosine (m6A) modification of mRNAs, plays key roles in diverse biological processes. Here, we found that the m6A “reader” YT521-B homology domain-containing family 3 (YTHDF3) suppresses ISG expression under basal conditions by promoting translation of the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 36 publications
1
111
1
Order By: Relevance
“…YTHDFs have many important biological functions [18]. For instance, YTHDF3 suppresses interferondependent antiviral responses by promoting FOXO3 translation in HREpiC cells [19] and YTHDF2 promotes lung cancer cell growth by facilitating translation of 6phosphogluconate dehydrogenase mRNA [20]. However, the manner in which YTHDF3 cooperates with YTHDF1 and YTHDF2 to promote the translation or decay of m 6 Amodified YAP mRNA in NSCLC remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…YTHDFs have many important biological functions [18]. For instance, YTHDF3 suppresses interferondependent antiviral responses by promoting FOXO3 translation in HREpiC cells [19] and YTHDF2 promotes lung cancer cell growth by facilitating translation of 6phosphogluconate dehydrogenase mRNA [20]. However, the manner in which YTHDF3 cooperates with YTHDF1 and YTHDF2 to promote the translation or decay of m 6 Amodified YAP mRNA in NSCLC remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The IDR of YTHDF2 also interacts with the deadenylase complex CCR4-NOT and, via the adaptor protein HRSP12, with the endoribonuclease RNase P/MRP (Park et al, 2019). However, since the affinity of isolated YTH domains for m 6 A-modified RNA is modest (0.1-5 mM; Li et al, 2014b;Luo and Tong, 2014;Theler et al, 2014;Xu et al, 2014Xu et al, , 2015Zhu et al, 2014), it is possible that the IDR participates in RNA binding in vivo, as suggested by the loss of mRNA binding in vivo of a mutant in human YTHDF3 containing a deletion in the IDR (Zhang et al, 2019c). In this regard, it is noteworthy that three Arabidopsis YTHDF proteins (ECT5, ECT9, and ECT10) contain an amino acid substitution expected to result in 10-fold higher affinity toward m 6 A RNA than other YTH domains, based on structural and biochemical analyses of analogous mutants in human YTHDF1 (Xu et al, 2015;Scutenaire et al, 2018).…”
Section: Reading M 6 Amentioning
confidence: 99%
“…Indeed, YTHDF3 has recently been shown to have roles in promoting translation of m 6 A-modified genes, perhaps by its interaction with proteins of the 40S and 60S ribosomal subunits (Li et al, 2017;Shi et al, 2017), and YTHDC2 can recognize m 6 A within coding sequence to enhance translation (Mao et al, 2019). Of note, others have found that YTHDF3 inhibits ISG production in murine models through its enhancement of FOXO3 translation, although this apparently occurred independently of m 6 A (Zhang et al, 2019b). Therefore, m 6 A and its related proteins can regulate ISG expression through a variety of mechanisms.…”
Section: Discussionmentioning
confidence: 99%